Answer:
7x+1
Step-by-step explanation:
Let's simplify step-by-step.
4x−5+3x+6
=4x+−5+3x+6
Combine Like Terms:
=4x+−5+3x+6
=(4x+3x)+(−5+6)
=7x+1
Hope this helps!
Numerical expressions contain numbers, while algebraic expressions contain variables and numbers.
<u>Numerical Expression</u>
"Difference" indicates that we'll be subtracting 13 from 48.
48 - 13 = 35
<u>Algebraic Expression</u>
Variables represent the unknown number, in this case the difference between 48 and 13. Let d represent the difference between the two.
48 - 13 = d
35 = d
Step-by-step explanation:
Given
![= {x}^{2} \times {x}^{ - 12 } \\ = {x}^{2 - 12} \\ = {x}^{ - 10}](https://tex.z-dn.net/?f=%20%3D%20%20%7Bx%7D%5E%7B2%7D%20%5Ctimes%20%20%7Bx%7D%5E%7B%20-%2012%20%7D%20%5C%5C%20%20%3D%20%20%7Bx%7D%5E%7B2%20-%2012%7D%20%20%20%20%5C%5C%20%20%3D%20%20%7Bx%7D%5E%7B%20-%2010%7D%20)
Hope it will help :)
Answer:
1) 2.3
2) 4.088
3) .416
4) 12.52
5) 1012.5
Step-by-step explanation:
U see I would help but just because u said “pwease” I’m not :)